2014
DOI: 10.1371/journal.pone.0107272
|View full text |Cite
|
Sign up to set email alerts
|

Association between DAPK1 Promoter Methylation and Cervical Cancer: A Meta-Analysis

Abstract: BackgroundDeath-associated protein kinase1 (DAPK1) is an important tumor suppressor gene. DNA methylation can inactivate genes, which has often been observed in the carcinogenesis of cervical cancer. During the past several decades, many studies have explored the association between DAPK1 promoter methylation and cervical cancer. However, many studies were limited by the small samples size and the findings were inconsistent among them. Thus, we conducted a meta-analysis to assess the association between DAPK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…In addition to HPV infection, particularly high-risk HPV genotypes, recently, the inactivation of TSGs due to promoter hypermethylation has been reported that it is a frequent mechanism plays an important criterion in cervical carcinogenesis [8,[14][15][16]. In this study, we demonstrated that the hypermethylation of the DAPK gene promoter was found in high frequency in high-risk HPV infected samples, counting for 66.67% (24 of 36 samples), compared to low-risk HPV infected samples, counting for 12.0% (3 of 25 samples) and non-HPV infected samples, counting for 2.08% (1of 48 samples).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to HPV infection, particularly high-risk HPV genotypes, recently, the inactivation of TSGs due to promoter hypermethylation has been reported that it is a frequent mechanism plays an important criterion in cervical carcinogenesis [8,[14][15][16]. In this study, we demonstrated that the hypermethylation of the DAPK gene promoter was found in high frequency in high-risk HPV infected samples, counting for 66.67% (24 of 36 samples), compared to low-risk HPV infected samples, counting for 12.0% (3 of 25 samples) and non-HPV infected samples, counting for 2.08% (1of 48 samples).…”
Section: Discussionmentioning
confidence: 99%
“…Additional genetic and epigenetic alterations are required for progression from precancerous disease to invasive cancer [8,12,13]. Among the putative molecular alterations involved in cervical carcinogenesis process, promoter hypermethylation, an important epigenetic modification, has long been found to be a major mechanism of inactivation of tumor suppressor genes (TSGs), which has been considered as an early epigenetic event in driving carcinogenesis of many human cancers, including cancer of cervix [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cervical cancer, the frequencies of DAPK1 promoter hypermethylation ranges from 30.0% to 78.6% (median, 59.3%) and is more pronounced in more advanced stages (Narayan et al, 2003). It can then be regarded as a valuable biomarker for cervical cancer development (Xiong et al, 2014).…”
Section: Genetic Aspects Of Tnbcmentioning
confidence: 99%